Pengaruh Biaya Produksi Dan Penjualan Terhadap Laba Perusahaan : (Studi Kasus Pada PT. Surya Utama Agrolestari Kota Jambi) - Ara Yustika Br.Ginting; Nur Ahmadi Bi Rahmani; Kusmilawaty Kusmilawaty (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the effect of production costs and sales on the profit of PT Surya Utama Agrolestari in 2017-2020. The type of research used is quantitative research with a deductive approach by having assumptions to test the theory. The data source used is secondary data with data analysis techniques that use classical assumption tests with normality, multicollinearity, heteroscedasticity and autocorrelation tests, the second is multiple linear regression tests and hypothesis testing with t tests, f tests and tests, so that in this study the data used are production costs, sales and company profits from 2017-2020 PT. Surya Utama Agrolestari. The results showed that there is a positive effect of production costs on company profits, which is known to have a significant value of 0.000 <0.05. Sales have a negative effect on company profits, which is known to be a significant value of 0.251> 0.05. Then production costs and sales together (simultaneously) have a positive and significant effect on company profits which is worth 0.000 <0.05.